Early Prevention Of Bullying At School: Nobully's Sociometric Approach - Rojabi Azharghany; Wahab Sya’roni (At-Tarbiyat, 2023)
This study aims to explore the effectiveness of Nobully's sociometric approach in preventing early bullying in the school environment. The aim of this research is to use a qualitative research design with a case study technique. Data was collected through participatory observation events, interviews with students and school staff, as well as analysis of documents connected to school policies. The study results show that the NoBully sociometric approach has a positive effect in creating a more inclusive school environment and reducing bullying incidents. The integration of these methods promotes the formation of healthier social relationships among students, increases awareness of the importance of empathy, and changes group dynamics to encourage positive responses to differences. These findings support that the application of the NoBully sociometric approach has the potential to be an effective strategy in early prevention of bullying in the school environment, providing a foundation for the development of more comprehensive programs in creating a safe and supportive learning environment for all students. By implementing the NoBully sociometric method, schools can create a more positive atmosphere, where students feel more comfortable, supported, and avoid the risk of bullying.